Duration of untreated illness predicts 3-year outcome in patients with obsessive-compulsive disorder: A real-world, naturalistic, follow-up study. (May 2021) - Perris, Francesco; Sampogna, Gaia; Giallonardo, Vincenzo; Agnese, Salvatore; Palummo, Carmela; Luciano, Mario; Fabrazzo, Michele; Fiorillo, Andrea; Catapano, Francesco
Highlights: Mean DUI was approximately 7 years with a mean age at onset of the disease of 22.3 years. Patients with symmetry cluster symptoms were younger at onset of the disease and had a longer DUI. DUI was not associated with gender, educational level, and with a family history of psychiatric disorders. Predictors of good outcome included DUI, insight, severity of OCD symptoms, not age at onset. Abstract: Duration of untreated illness (DUI) is a predictor of outcome in psychotic and affective disorders. The few available data on the effect of DUI in obsessive-compulsive disorder (OCD) suggest an association between longer DUI and poorer response to treatments. This is a real-world, naturalistic, follow-up study evaluating the impact of DUI on long-term clinical outcomes. The sample consists of 83 outpatients with OCD with a mean DUI of 7.3 (5.8) years. Patients with symmetry/ordering cluster symptoms were younger at onset of the disease (20.4 ± 7.9 vs. 27.8 ± 10.6; p <.05, d = 0.79), had a longer duration of the illness (10.1 ± 4.6 vs. 6.8 ± 4.6, p <.05; d = 0.53) and a longer DUI (7.9 ± 6.5 vs. 5.4 ± 3.6, p <.05, d = 0.49) compared to patients not presenting with those symptoms. Fifty-nine patients completed the follow-up, and 33.9% ( N = 20) met the criteria for partial remission, scoring <15 at the Y-BOCS for at least eight weeks. Patients in partial remission for more than 40% of the follow-up were defined as "good outcome" and they had a significantly shorter DUI compared to patients with "poor outcome". Access to adequate treatments is highly delayed in patients with OCD. DUI is strongly associated with poor treatment outcomes. Therefore, strategies to ensure an early diagnosis and treatment are needed.